Standardization of blood smears prepared in transparent acetate : an alternative method for the microscopic diagnosis of malaria - Mello, Marcia B. C. (2014)
Background: Due to students’ initial inexperience, slides are frequently broken and blood smears are damaged in microscopy training, leading to the need for their constant replacement. To minimize this problem a method of preparing blood smears on transparent acetate sheets was developed with the goal of implementing appropriate and more readily available teaching resources for the microscopic diagnosis of malaria. Methods: Acetate sheets derived from polyester were used to standardize the preparation and staining of thin and thick blood smears on transparent acetate sheets. Thick and thin blood smears were also prepared using the conventional method on glass slides. The staining was conducted using Giemsa staining for the thick and thin smears. Results: Microscopic examination (1,000x) of the thin and thick blood smears prepared on transparent acetate produced high-quality images for both the parasites and the blood cells. The smears showed up on a clear background and with minimal dye precipitation. It was possible to clearly identify the main morphological characteristics of Plasmodium, neutrophils and platelets. After 12 months of storage, there was no change in image quality or evidence of fungal colonization. Conclusion: Preparation of thin and thick blood smears in transparent acetate for the microscopic diagnosis of malaria does not compromise the morphological and staining characteristics of the parasites or blood cells. It is reasonable to predict the applicability of transparent acetate in relevant situations such as the training of qualified professionals for the microscopic diagnosis of malaria and the preparation of positive specimens for competency assessment (quality control) of professionals and services involved in the diagnosis of malaria.